Effect of thermal treatments and non‐starch fraction on in vitro starch digestibility of oat bran. Issue 12 (6th October 2022) - Bai, Xue; Zhang, Meili; Zhang, Yakun; Zhang, Yuanyuan; Guo, Xinyue; Huo, Rui
Abstract: The effects of removing non‐starch constituents like lipids, proteins, and β ‐glucan on the in‐vitro digestibility of oat bran by steaming, microwaving, and hot air drying were investigated in this study. The results showed that the rapidly digestible starch (RDS) content of steaming oat bran decreased significantly ( p < 0.05), and the glycemic index (e GI) was the lowest (66.11). The resistant starch (RS) content decreased, and in vitro digestibility, hydrolysis index, and eGI values of pretreated oat bran increased after removing the non‐starch constituents. Lipid removal increased in vitro digestibility the most, followed by β ‐glucan and protein removal. The solubility of oat bran with removing protein increased significantly after steaming and microwaving treatment ( p < 0.05). The relative crystallinity of oat bran decreased during steaming and increased after microwave and hot air drying. In conclusion, co‐existed components like proteins, fiber and lipids are helpful to a purpose of a low GI and slow starch digestion. Practical applications: In this study, high value‐added utilization of oat bran was realized, which solved the problems of resource waste and environmental pollution. Meanwhile, the steaming oat bran with intact structure is helpful for a purpose of low GI and slow starch digestion and is more beneficial to human health.